CAR-T cell therapy: breakthroughs, challenges and emerging horizons in cancer treatment - Goel, Rajeev (International Journal of Research in Medical Sciences, 2024)
Chimeric Antigen Receptor (CAR)-T cell therapy has recently emerged as a breakthrough technology, offering a targeted approach in the treatment of cancers. It is a form of cancer immunotherapy which involves genetic modification of autogenic or allogenic T cells to express a chimeric receptor that can target a specific tumor antigen on the malignant cells. The receptors are chimeric because both antigen-binding and T cell activating functions are integrated into a single receptor. The greatest potential of CAR-T cell therapy lies in its power to use the patient’s immune system to fight cancer besides its durability. It also overcomes certain limitations such as limited effectiveness in resistant cancers, lack of precision in blood cancers etc. associated with the traditional cancer therapies like chemotherapy and radiation. CAR-T cell therapy has proven significantly efficacious in clinical trials for the treatment of patients with relapsed or refractory haematological malignancies and to a lesser extent in solid tumors too. A few of these CAR- T cells therapies have finally been approved by the FDA after decades of pre-clinical developments. CAR-T cell therapy though causes long term remissions in some cancer patients, yet few patients either relapse after the therapy or suffer severe toxic and adverse effects, leaving innovation space for further research. This review discusses the structure of CAR-T cells, principle of CAR-T cell therapy and its clinical applications, efficacy, safety, challenges and future directions for its use in cancer patients.